Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Louvrea Kosmetik - Hayuan Banowati; Irwan Raharja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of promotion and service quality on customer satisfaction. This research was conducted on Louvrea cosmetic customers. The population in this study were Louvrea cosmetics customers, while the samples that met the observation sampling criteria were 100 respondents. The data collection technique in this study used the slovin technique. Data analysis techniques in this study using the t test and hypothesis testing. The results showed that the promotion variable partially did not have a significant effect on customer satisfaction, the service quality variable partially had a significant effect on customer satisfaction and based on the hypothesis test regarding the effect of promotion and service quality on customer satisfaction simultaneously there was a significant effect between promotion and service quality on satisfaction customers on Louvrea products.